A High-Resolution Remote-Sensing-Based Method for Urban Ecological Quality Evaluation - Huang, Huiping; Li, Qiangzi; Zhang, Yuan (Frontiers in Environmental Science, 2022)
Ecological quality evaluation is essential for urban land use and ecosystem planning due to the rapid urbanization and population growth. However, accurate and efficient evaluation of urban ecological quality is challenging, as traditional remote-sensing-based methods focus mainly on low spatial resolution data, pixel-based land cover classification, and vegetation condition, and ignore the object-oriented classification and landscape pattern. A high-resolution remote-sensing-based method for urban ecological quality evaluation is greatly needed to support spatially explicit decision-making in urban planning. In this study, we developed six ecological indicators based on vegetation conditions and landscape patterns for evaluating urban ecological quality. Unlike traditional indicator acquisition methods, the six ecological indicators were derived from high-resolution remote sensing data using an object-oriented land cover classification method. The factor analysis using all six indicators as input to evaluate ecological quality indicated that the contribution of landscape patterns is weakened. Therefore, vegetation condition and landscape pattern were used as two variables to build a linear model, with their weights calculated from the loadings of factor analysis. The results show that the proposed linear model, with both vegetation conditions and landscape patterns considered, is effective in evaluating urban ecological quality. The results of the study can provide further support to urban land use and ecological planning.